A new species of Tontelea from Amazonian Peru and Ecuador, and notes on the Tontelea attenuata species group (Celastraceae, Hippocrateoideae) - Lombardi, J. A. (New York Botanical Garden, 2006)
Tontelea fuliginea differs from other species whose stamens alternate with undivided stigma-lobes by its profusely ramified, many flowered, and densely dirty-brown puberulous inflorescences. This paper also provides a synopsis and key of the group of species with alternate stamens and 3-lobed stiomas with undivided lobes (T. attenuata group). Four lectotypes are designated for previously published names: Tontelea longifolia, Tontelea micrantha, Tontelea corrugulata, and Salacia micrantha var. lancifolia.
Keywords: Tontelea; Hippocrateoideae; Celastraceae; Peru; Ecuador; systematics